ATRIBUT LUXURY HOTEL DI JAKARTA BERDASARKAN ULASAN DIGITAL PADA TRIPADVISOR - Rachel Dyah Wiastuti; Josephine Rosalia Kurnia (Pringgitan, 2021)
This research aims to determine the customer’s satisfaction and dissatisfaction faktor on the luxury hotel in Central Jakarta based on online review at TripAdvisor platform. This research uses qualitative descriptive approach with content analysis. Two objects for this research are Hotel Indonesia Kempinski Jakarta and Keraton at The Plaza Hotel, Jakarta. However, the research samples are 1,229 excellent reviews that represent customer satisfaction and 31 terrible reviews that represent customer dissatisfaction. Findings reveals that room quality valued 17.4% as the determinant faktors of customer satisfaction in the luxury hotel. Room quality are considered as spacious room space, proper amenities, and latest technology equipment such as universal power socket and iPod charging dock. On the other hand, service quality valued 21.15% as the determinant faktors of customer dissatisfaction in the luxury hotel. Service quality are considered as unresponsive employee, lack of employee product knowledge, and unpolite employee. Luxury hotel premises are expected to always maintain hotel cleanliness and professional employee to ensure customer satisfaction. Further research should emphasize on other hotel category and use more online platform to gather more reviewsKeywords: Hotel Attributes, Luxury Hotel, Online Review, Satisfaction Factors